Amyloid-β Peptides and Tau Protein as Biomarkers in Cerebrospinal and Interstitial Fluid Following Traumatic Brain Injury: A Review of Experimental and Clinical Studies - Tsitsopoulos, Parmenion P.; Marklund, Niklas (Frontiers in Neurology, 2013)
Traumatic brain injury (TBI) survivors frequently suffer from life-long deficits in cognitive functions and a reduced quality of life. Axonal injury, observed in most severe TBI patients, results in accumulation of amyloid precursor protein (APP). Post-injury enzymatic cleavage of APP can generate amyloid-β (Aβ) peptides, a hallmark finding in Alzheimer’s disease (AD). At autopsy, brains of AD and a subset of TBI victims display some similarities including accumulation of Aβ peptides and neurofibrillary tangles of hyperphosphorylated tau proteins. Most epidemiological evidence suggests a link between TBI and AD, implying that TBI has neurodegenerative sequelae. Aβ peptides and tau may be used as biomarkers in interstitial fluid (ISF) using cerebral microdialysis and/or cerebrospinal fluid (CSF) following clinical TBI. In the present review, the available clinical and experimental literature on Aβ peptides and tau as potential biomarkers following TBI is comprehensively analyzed. Elevated CSF and ISF tau protein levels have been observed following severe TBI and suggested to correlate with clinical outcome. Although Aβ peptides are produced by normal neuronal metabolism, high levels of long and/or fibrillary Aβ peptides may be neurotoxic. Increased CSF and/or ISF Aβ levels post-injury may be related to neuronal activity and/or the presence of axonal injury. The heterogeneity of animal models, clinical cohorts, analytical techniques and the complexity of TBI in available studies make the clinical value of tau and Aβ as biomarkers uncertain at present. Additionally, the link between early post-injury changes in tau and Aβ peptides and the future risk of developing AD remains unclear. Future studies using e.g. rapid biomarker sampling combined with enhanced analytical techniques and/or novel pharmacological tools could provide additional information on the importance of Aβ peptides and tau protein in both the acute pathophysiology and long-term consequences of TBI.